Ways to Apply the Electronic Systems and Using Them to Meet the Efficiency Standards in the Department of Computer at Tragen College and to Highlight the Obstacles - Matoug, Mohamed; Mare, Fatimah; Alsonosi, Kamal (Journal of Pure & Applied Sciences, 2018)
There has been a revolution in technology that characterises the new era; that is, the new technology is dominating every different area in the institutions of higher education. Based on the humbly available abilities, It is becoming clearly obvious that Tragen College, and particularly the department of computer science, which is meant to be the most powerful of any technological support, is in serious need to apply technology to meet the efficiency in the education process. This study aims to reveal the computer department policies towards introducing the ways of perfectly using technical systems that are presented by last year's students to computerise the manual tasks as well as improve the efficiency in the services. There are many projects whose goal is to present the possible solutions for a variety of problems in departments at Tragen College; however, they are not perfectly and effectively exploited. This study is going to highlight the computer department strategies to apply these systems and to track technological development. It will also show the sample of these systems that are already in use (for instance, the project of enrolment and results statistics, the electronic mid-test system, the placement test system to register for Sebha University, and the project for assessing the staff and curriculums). In addition, this study aims to show the obstacles that prevent applying these projects in the college.